2006
DOI: 10.1111/j.1467-9817.2006.00301.x
|View full text |Cite
|
Sign up to set email alerts
|

Relations between socio‐cultural factors, the home literacy environment and children's literacy development in the first years of primary education

Abstract: This paper deals with the relation between children's home literacy environments (HLE) and their literacy development in the first phase of primary school. On the basis of a broad conceptualisation of the HLE, we identified three home literacy profiles (rich, child-directed and poor HLE). Firstly, we related these profiles to socio-cultural factors (more specifically, ethnicity and socio-economic status [SES]). We found an association between the HLE and ethnicity/SES, indicating that (Dutch) majority children… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
163
1
37

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 222 publications
(209 citation statements)
references
References 29 publications
8
163
1
37
Order By: Relevance
“…Os autores concluíram que todo modelo compreensivo para a aquisição da leitura deve considerar as variáveis peculiares ao país, à família, à escola e às características individuais (como a motivação para a leitura). De maneira análoga, Steensel (2006) mostrou que uma medida do envolvimento do ambiente familiar no letramento causou um efeito no vocabulário da criança e na compreensão da leitura. Enfim, Duncan e Seymour (2000) mostraram que crianças escocesas de baixo nível socioeconômico tiveram um atraso na aquisição da habilidade de leitura em relação aos seus pares de alto nível socioeconômico.…”
unclassified
“…Os autores concluíram que todo modelo compreensivo para a aquisição da leitura deve considerar as variáveis peculiares ao país, à família, à escola e às características individuais (como a motivação para a leitura). De maneira análoga, Steensel (2006) mostrou que uma medida do envolvimento do ambiente familiar no letramento causou um efeito no vocabulário da criança e na compreensão da leitura. Enfim, Duncan e Seymour (2000) mostraram que crianças escocesas de baixo nível socioeconômico tiveram um atraso na aquisição da habilidade de leitura em relação aos seus pares de alto nível socioeconômico.…”
unclassified
“…I maintain that a HLE consists of a number of activities that children observe at home and activities in which parents participate actively. A HLE also includes parental beliefs regarding literacy, the parental education level, the family socioeconomic status, the number of books at home, and daily life activities in the social domains (Auerbach, 1989;Teale, 1986;van Steensel, 2006).…”
mentioning
confidence: 99%
“…Children that manage to attend government schools make poor progress and eventually drop out because of low literacy levels (Button & Johnson, 1997;Bus, Van Ijzendoorn & Pellegrini, 1995;Mol, Bus & De Jong, 2009), lack of teacher support (Morrow, 2001;Van Steensel, 2006), underrepresentation in schools (Jones & Ramchand, 2016;Olgun, Gumus & Adanacioglu, 2010) and the lack of pedagogic attention to language acquisition (Gelda, 2013;Nambeesan, 1996;Shanbhag, 2016).…”
Section: Language and Literacymentioning
confidence: 99%
“…As the findings of this research revealed, children cannot progress and complete primary education without acquiring basic literacy. School curriculum, resources and teachers play an immense role in ensuring the progress of children, because of which the development of literacy skills in early childhood education is of utmost importance (Morrow, 2001;Van Steensel, 2006 OER curation "offers cheap and simple ways for small-scale open education projects to be effective and sustainable" (Rolfe, 2016, p.297). Scholarly works suggest that in a rapidly changing sphere, curation is becoming an indispensable filtering step for OER providers as it can save users from having to go through laborious manual filtering and selection processes over the internet (Perryman & Coughlan, 2014;Porcello & Hsi, 2013;Atkins, Brown & Hammond, 2007).…”
Section: Recommendationsmentioning
confidence: 99%
See 1 more Smart Citation